Pengaruh Kualitas Pelayanan Dan Bagi Hasil Terhadap Keputusan Menabung Pada Nasabah Di Bank Syariah Indonesia Cabang Rogojampi - Indana Almas Azhar; Nila Alfiatul Fuad; Ribut Suprapto (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The purpose of this study is to determine whether: 1) knowing the quality of service and profit sharing on the customer's saving decision at the same time has a positive effect and significance 2) Knowing the impact of quality of service and profit sharing on the customer's saving decision partially has a positive effect and significance. Ha (1): There is the effect of service quality and profit sharing partially on customers' saving decisions at Bank Syariah Rogojampi. ha (2) There is a simultaneous influence of service quality and profit sharing on customers' saving decisions at Bank Syariah in Rogojampi. The conclusion of the partial and simultaneous results is that there is a positive influence between the variables X1 (quality of service), X2 (profit sharing), and Y (saving decision) with an R of 0.745 and a significance of 20.544 > 3.28.